PENGARUH TINDAK AGRONOMI DAN LINGKUNGAN TERHADAP HASIL PADI LOKALKULTIVAR SIAM UNUS PADA TIGA KECAMATAN DI KABUPATEN BARITO KUALA - Fadliah Fadliah; Bambang F. Langai; Raihani Wahdah (EnviroScienteae, 2018)
Research on Agronomic and Environmental Measures to Local Paddy Cultivars Siam Unus on Three Districts in Barito Kuala Regency from December 2017-January 2018. The research method used was survey method, and data collection method used is purposive sampling, that farmer which rice plant of local varieties Siam Unus, and 2 villages in 3 sub-districts, and each village was selected random samples each of 10 farmers with the interview with local rice farmer Siam Unus located at the location. farmers who used the tractor in the tidal area were 8 people (13.33%) and those who did not use the tractor for the tidal area were 52 people (88.67%). Local farmers who use lime as many as 26 people (43.33%), and who do not use lime for his farm as much as 34 people (56.67%). Due to the land used to grow local paddy was flooded with high water. The direct influence of rainy days and rainfall in tidal swamps to the productivity of local varieties of Siam Unus rice each gives negative influence and contribution of 1.11% and 2.90% to the productivity of local rice plants varieties Siam Unus.